Facile ultrasonication synthesis of MXene/HKUST-1 composite as positive electrode for supercapattery - Ismail, Rashidah; Azman, Nur Hawa Nabilah; Mohanadas, Dharshini; Mustafa, Muhammad Norhaffis; Mohd Abdah, Muhammad Amirul Aizat; Raman, Velan; Abdullah, Jaafar; Sulaiman, Yusran (Elsevier, 2024)
Supercapattery is an energy storage device that can overcome the sustainable energy and environmental crisis with the advantage of enhanced specific power and specific energy. A facile ultrasonication method was used to synthesise a composite of MXene and HKUST-1 (MXene/HKUST-1). MXene/HKUST-1 composite was studied for its morphology, phase, vibration mode, functional groups, chemical composition and surface area that contributed to the electrochemical performance. Pairing MXene/HKUST-1 as a positive electrode with activated carbon (AC) as a negative electrode in a supercapattery device achieved Cs of 19 C g−1 and a specific energy of 4.0 Wh kg−1. The specific power of the device was 348 W kg−1 and the stability was 65% after 10,000 cycles. The highly conductive MXene, large surface area and porosity of HKUST-1 create a remarkable performance of the supercapattery device by mitigating the self-restacking problem in MXene and low conductivity of HKUST-1.